Full Mouth Rehabilitation of the Maxilla and Mandible with Implant- Supported Prostheses: A Case Report - Shrestha, S; Singh, R; Prajapati, R; Shrestha, B (Journal of Nepalese Prosthodontic Society, 2024)
The placement of dental implants in severely atrophic arches is not a straight-forward procedure. In such situations, the All-on-four protocol provides a simple alternative. The placement of four implants— two straight and two tilted— in these clinical scenarios allows clinicians to place fixed provisional restorations that are immediately loaded, and the patient can function with. This approach results in more simplicity, less treatment time, less patient morbidity, and immediate function. The provisional restoration is replaced by the permanent restoration after the period of osseointegration. Furthermore, incorporating surgical guides in the treatment allows for precise and controlled placement of implants that is confirmed during the treatment planning stage.